2020
DOI: 10.1038/s42003-020-01369-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic networks observed in the nucleosome core particles couple the histone globular domains with DNA

Abstract: The dynamics of eukaryotic nucleosomes are essential in gene activity and well regulated by various factors. Here, we elucidated the internal dynamics at multiple timescales for the human histones hH3 and hH4 in the Widom 601 nucleosome core particles (NCP), suggesting that four dynamic networks are formed by the residues exhibiting larger-scale μs-ms motions that extend from the NCP core to the histone tails and DNA. Furthermore, despite possessing highly conserved structural features, histones in the telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 57 publications
(72 reference statements)
3
40
0
Order By: Relevance
“…Subsequent MAS NMR studies of mononucleosomes by Shi et al also confirmed these observations ( Shi et al, 2018 ). This discrepancy is most likely due to the type of experiments used (i.e., sidechain vs. backbone correlations), with 13 C MAS NMR experiments holding a slight advantage regarding the detection of slower moving tail sidechains such as those that are close to the DNA interface ( Shi et al, 2018 ; Shi et al, 2020b ). While the detected tail boundary is consistent between arrays and mononucleosomes in MAS NMR experiments, a closer look into the 15 N spin relaxation rates of H3 tails reveals mobility differences ( Zandian et al, 2021 ).…”
Section: Mas Nmr Of Histone Tailsmentioning
confidence: 99%
“…Subsequent MAS NMR studies of mononucleosomes by Shi et al also confirmed these observations ( Shi et al, 2018 ). This discrepancy is most likely due to the type of experiments used (i.e., sidechain vs. backbone correlations), with 13 C MAS NMR experiments holding a slight advantage regarding the detection of slower moving tail sidechains such as those that are close to the DNA interface ( Shi et al, 2018 ; Shi et al, 2020b ). While the detected tail boundary is consistent between arrays and mononucleosomes in MAS NMR experiments, a closer look into the 15 N spin relaxation rates of H3 tails reveals mobility differences ( Zandian et al, 2021 ).…”
Section: Mas Nmr Of Histone Tailsmentioning
confidence: 99%
“…First, in order to probe the conformation and dynamics of the H4 tail in the tightly compacted and precipitated arrays, we collected 1 H- 13 C/ 15 N correlation ssNMR spectra in order to detect those AAs in the H4 tail region, which exhibits significant mobility compared with the rigid core region 45 , 46 . By using the known averaged chemical shift values of AAs combined with three-dimensional (3D) solution-state NMR experiments of the histone H4 in a Widom “601” nucleosome core particle 47 , we established the tail peak chemical shift assignments. Interestingly, two peaks, 3.50–62.4 ppm and 3.45–62.8 ppm, were observed in the 1 H− 13 C spectra of the nucleosome arrays containing H4K20me0 or H4K20me3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6e and Supplementary fig. 15a, b ), we obtained information about the internal dynamics of the H4 protein backbone at the μs-ms timescale 47 , 49 . In comparison with the H4K20me0 nucleosome array, the globular domain of the H4K20me1 array showed more uniform peak intensities across the protein and reduced relative intensities for several residues primarily residing in the LN and L1 regions and in the adjacent stretch of the α1 and α2 regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of long range dynamic correlations throughout the nucleosome observed here, which is a result of both DNA unwrapping and H2A.B substitution altering protein/protein and protein/DNA contacts, may play an additional role in epigenetic regulation. Indeed, allosetric networks within the nucleosome have been observed with solid state NMR experiments (86), and it has been proposed that epigenetic regulators may take advantage of these networks to influence genetic activity (87). Furthermore, it has been shown that allosteric transmission can be exploited to design drugs that bind at sites on the nucleosome surface (88), and that these networks can extend between nucleosomes to alter chromatin fiber dynamics (89).…”
Section: H2ab Reduces Long Range Dynamic Correlationsmentioning
confidence: 99%